Micromonospora schwarzwaldensis sp. nov., a producer of telomycin, isolated from soil - Vela Gurovic, Maria Soledad (2013)
A Gram-positive, spore-forming actinomycete strain (HKI0641T) was isolated from a soil sample collected in the Black Forest, Germany. During a screening for antimicrobial natural products this bacterium was identified as a producer of the antibiotic telomycin. Morphological characteristics and chemotaxonomic data suggested that the strain belongs to the genus Micromonospora. The peptidoglycan contains meso-diaminopimelic acid, and the fatty acid profile consists predominantly of anteiso-C15:0, iso-C15:0, iso-C16:0 and C16:0. MK-10(H4), MK-10(H2) and MK-10 were identified as the major menaquinones. To determine the taxonomic positioning of strain HKI0641T, we computed a binary tanglegram of two rooted phylogenetic trees that were based upon 16S rRNA and gyrB gene sequences, respectively. The comparative analysis of the two common classification methods strongly supported the phylogenetic affiliation with the genus Micromonospora, but it also revealed discrepancies in the assignment at the level of the genomic species. 16S rRNA gene sequence analysis identified M. coxensis DSM 45161T (99.1%) and M. marina DSM 45555T (99.0%) as the nearest taxonomic neighbours, whereas the gyrB sequence of strain HKI0641T indicated a closer relationship to M. aurantiaca DSM 43813T (95.1%). By means of DNA-DNA hybridization experiments, it was possible to resolve this issue and to clearly differentiate strain HKI0641T from other Micromonospora species. The type strains of the aforementioned Micromonospora species could be further distinguished from strain HKI0641T by several phenotypic properties, such as colony colour, NaCl tolerance and the utilization of carbon sources. The isolate was therefore assigned to a new species, for which the name Micromonospora schwarzwaldensis sp. nov. is proposed. The type strain is HKI0641T (= DSM 45708T = CIP 110415T).